Study of the Mesosphere and Lower Thermosphere by the Method of Creating Artificial Periodic Irregularities of the Ionospheric Plasma - Nataliya V. Bakhmetieva; Gennadiy I. Grigoriev (Atmosphere, 2022)
This article presented a brief review of studies of the Earth’s ionosphere at the heights of the mesosphere and lower thermosphere by a method based on the creation of artificial periodic inhomogeneities (APIs) of the ionospheric plasma by high-frequency radiation from powerful thermal installations. APIs are created by a standing wave due to the interference between upward-propagating radio waves and those reflected from the ionosphere. API studies of the ionosphere were based on Bragg scattering of probing impulse signals from an artificial periodic structure. The method makes it possible to measure the parameters of the neutral and ionized components of the Earth’s atmosphere. Note that, despite the fact that the API method assumes an artificial perturbation of the ionospheric plasma, the parameters of the mesosphere and lower thermosphere are determined at the stage of inhomogeneity relaxation and characterize the undisturbed medium. To date, periodic inhomogeneities have been observed at the heating points of Zimenki and Sura ionospheric heating facility (SURA, Vasilsursk, Russia), Gissar (Tajikistan), Arecibo (Puerto Rico, USA), High Power Auroral Stimulation Observatory (HIPAS) and High Frequency Active Auroral Research Program (HAARP, Gakona, AK, USA), and European Incoherent Scatter (EISCAT, Tromso, Norway). Most of the API studies of the ionosphere were carried out at the SURA mid-latitude heating facility (56.1° N; 46.1° E). The review presented the main results of determining the parameters of the ionosphere and neutral atmosphere at altitudes of 60–120 km and studies of the atmosphere during sunrise and sunset events and solar eclipses. In fact, the review is far from a complete illustration of the possibilities of using the API method to study the mesosphere and lower thermosphere.